Factors influencing Chinese folk music transmission via the Douyin short video platform: a grounded theory perspective - Runnan Zou; Liping Jiang (Frontiers in Communication)
IntroductionGiven the popularity of the Internet and short - video platforms, the transmission of folk music has undergone significant transformation in the digital age. However, research in this area has not kept pace with modernization, leaving a gap in understanding the key factors affecting folk music transmission in this new context.MethodsThis study entailed qualitative interviews with 20 folk music fans and two music bloggers on Douyin. The collected data were analysed using a grounded theory approach.ResultsThe study aimed to identify the key factors affecting folk music transmission. The findings indicated that there are factors influencing folk music transmission at different levels. At the macroscopic level, social culture and technological innovation have a significant impact on folk music transmission. At the mesoscopic level, the platform’s characteristics and the form and content of transmission are additional influencing factors. At the microscopic level, fan and blogger characteristics also play a role.DiscussionThis research not only enhances the theoretical understanding of folk music transmission on digital platforms but also provides practical insights for creators and platform planners. Specifically, the study highlights the importance of integrating high – quality content, innovative elements, and platform – specific characteristics.